+0  
 
0
85
1
avatar

The difference of the roots of the quadratic equation x^2 + bx + c = 0 is |b - 2c|. If c is not equal to 0, then find c in terms of b.

 Mar 17, 2020
 #1
avatar+21645 
0

Using the quadratic formula:

x2 + bx + c  =  0     --->     x  =  [ -b +/- sqrt(b2 - 4c) ] / 2

 

Difference of the roots:  | [ (-b + sqrt(b2 - 4c) / 2 ] - [ (-b - sqrt(b2 - 4c) / 2 ] |  =  | 2sqrt(b2 - 4c) / 2 |  =  sqrt(b2 - 4c)

 

But:  sqrt(b2 - 4c)  =  | b - 2c |

squaring both sides:  b2 - 4c  =  (b - 2c)2

                                  b2 - 4c  =  b2 - 4bc + 4c2

                                        -4c  =  -4bc + 4c2 

                                           0  =  4c2 + 4c - 4bc

                                           0  =  c2 + c - bc

                                           0  =  c(c + 1 - b)

Either  c = 0  or  c + 1 - b  =  0

Since  c is not equal to 0,  c = b - 1

 Mar 17, 2020

25 Online Users

avatar
avatar
avatar
avatar
avatar